Chapter 2: Economics or politics? Assessing immigration as a challenge to the welfare state - Eger, Maureen A. (Edward Elgar Publishing, 2022)
This chapter assesses the extent to which immigration poses a challenge to the welfare state. To do this, I synthesize previous scholarship from economics, political science, and sociology to evaluate the economic and political implications of immigration for welfare states. Contrary to the fiscal burden and welfare magnet hypotheses, the most recent cross-national and longitudinal studies indicate that, on average, immigration's net fiscal impact is positive,Äîalbeit small. However, research on the political impact of immigration does provide evidence that immigration creates challenges for welfare states in regards to welfare attitudes, support for left parties, and redistributive social policies.